Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Khusus terhadap Indeks Pembangunan Manusia pada Kabupaten dan Kota di Provinsi Lampung tahun 2016-2019 - Eka Jatmiko Sulistio Wati; Eksa Ridwansyah; Anita Kusuma Dewi (Jurnal Ilmiah ESAI, 2023)
This study aims to determine the effect of local revenue and special allocation funds on the human development index. This study uses a non-probability sampling technique, namely saturated samples. The population used in this study were 15 districts and cities in Lampung Province. This study uses secondary data from www.bps.go.id. Data analysis used descriptive analysis test, classical assumption test, multiple linear analysis test, coefficient of determination test, and t test (partial) with the test tool used was SPSS.V.25.0. The results of this study indicate that Local Revenue has an effect on the Human Development Index while for the variable Special Allocation Funds have no effect on the Human Development Index.